Ethics of Belief, Trust and Epistemic Value: The Case of the Scientific Controversy Surrounding the Measles Vaccine - Sauvayre, Romy (Journal of Leadership, Accountability and Ethics, 2021)
An anxious belief that the vaccine against measles may cause autism in children has circulated since 1998. This belief has resulted in a worldwide reduction of vaccination coverage. Between 1998 and 2004, the scientific community was engaged in an intense debate over proof of vaccine safety. The question is then to examine the justification and the acceptance of this anxious belief by scientists, journalists, and parents. What are the epistemic obligations of individuals when scientific evidence is lacking? Therefore, the ethics of belief will be questioned through a contemporary socio-historical case study because it permits the examination of belief, knowledge and confidence mechanisms, and the attribution of epistemic values when it is difficult to produce indisputable evidence.